E-beam direct synthesis of macroscopic thick 3D porous graphene films. (September 2021) - Han, Shuai; Li, Nian; Song, Yanping; Chen, Liqing; Liu, Cui; Xi, Min; Yu, Xinling; Qin, Yi; Xu, Tingting; Ma, Cheng; Zhang, Shudong; Wang, Zhenyang
Abstract: Three dimensional (3D) porous graphene can prevent restacking of graphene sheets and enables easy access and diffusion of ions, which affords possibility to fill the gap between laboratory research and industrialization of graphene. However, efficient synthesis of macroscopic thick 3D porous graphene films is still a challenge. Here, a novel strategy is firstly reported to straightforward synthesize 3D graphene, by high-energy e-beam induction on polyimide (PI). Due to high kinetic energy and low reflection features, energy of e-beam can be readily absorbed, leading to carbonization of PI and formation of macroscopic thick graphene films (0.66 mm) with abundant 3D pore structures and desirable electrical conductivity of 1100 S m −1 . Meanwhile, the few-layer structure, low defects, high quality, and rapid synthesis speed (84 cm 2  min −1 ), enable the as-obtained e-beam induced graphene (EIG) film to possess the potential for large-scale applications. Performances of EIG in energy storage and photothermal deicing have been explored. The EIG supercapacitor shows an impressive specific areal capacitance of 67.1 mF cm −2  at 0.1 mA cm −2 . Besides, EIG exhibits desirable and eco-friendly photothermal deicing capability at −40 °C. This methodology exhibits wide applicability in pursuing concepts of fast, simple and low-cost for 3D graphene manufacturing and multidisciplinary applications. Graphical abstract: A novel strategy of rapid and straightforward synthesis of macroscopic thick 3D porous graphene by high energy e-beam induction. Image 1 Highlights: High energy e-beam is used to directly synthesize graphene for the first time. E-beam induced graphene (EIG) is high-quality 3D graphene with porous network. EIG film shows a macroscopic thickness of 662 μm. The rapid synthesis speed of EIG film is up to 84 cm 2  min −1 . Performance in energy storage and photothermal deicing of EIG is investigated.